Peningkatan Pemahaman Wajib Pajak Orang Pribadi melalui Pelatihan Pengisian SPT Tahunan Orang Pribadi bagi Karyawan PT BSI Pro Jakarta - Trinik Susmonowati (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
The community service program that is carried out aims to provide training as an effort to increase understanding of taxation, especially reporting and filling in the Annual Income Tax Notice (SPT) for individual taxpayers intended for PT BSI Pro employees. This training is aimed at realizing an understanding of the importance of taxes and the importance of citizen participation in creating a tax-aware society. An e-Filing Training was conducted to provide staff of PT BSI Pro to be able to fill e-Filing smoothly. The method used includes: question and answer, and simulation/practice of filling e- Filing. The results achieved were the staff of PT BSI Pro: (1) having an adequate understanding of filling e-Filing, and (2) having the ability to complete e-Filing.